Green Synthesis of Silver Oxide Nanoparticles from Mauritia flexuosa Fruit Extract: Characterization and Bioactivity Assessment - Johana Zúñiga-Miranda; David Vaca-Vega; Karla Vizuete; Saskya E. Carrera-Pacheco; Rebeca Gonzalez-Pastor; Jorge Heredia-Moya; Arianna Mayorga-Ramos; Carlos Barba-Ostria; Elena Coyago-Cruz; Alexis Debut; Linda P. Guamán (Nanomaterials)
The increasing prevalence of multidrug-resistant (MDR) pathogens, persistent biofilms, oxidative stress, and cancerous cell proliferation poses significant challenges in healthcare and environmental settings, highlighting the urgent need for innovative and sustainable therapeutic solutions. The exploration of nanotechnology, particularly the use of green-synthesized nanoparticles, offers a promising avenue to address these complex biological challenges due to their multifunctional properties and biocompatibility. Utilizing a green synthesis approach, Mauritia flexuosa Mf-Ag2ONPs were synthesized and characterized using dynamic light scattering (DLS), transmission electron microscopy (TEM), X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy coupled with scanning electron microscopy (EDS-SEM), UV-Vis spectroscopy, and Fourier transform infrared spectroscopy (FTIR). The Mf-Ag2ONPs exhibited potent antibacterial effects against both non-resistant and MDR bacterial strains, with minimum inhibitory concentrations (MICs) ranging from 11.25 to 45 µg/mL. Mf-Ag2ONPs also demonstrated significant antifungal efficacy, particularly against Candida glabrata, with an MIC of 5.63 µg/mL. Moreover, the nanoparticles showed strong biofilm inhibition capabilities and substantial antioxidant properties, underscoring their potential to combat oxidative stress. Additionally, Mf-Ag2ONPs exhibited pronounced anticancer properties against various cancer cell lines, displaying low IC50 values across various cancer cell lines while maintaining minimal hemolytic activity at therapeutic concentrations. These findings suggest that Mf-Ag2ONPs synthesized via an eco-friendly approach offer a promising alternative for biomedical applications, including antimicrobial, antifungal, antioxidant, and anticancer therapies, warranting further in vivo studies to fully exploit their therapeutic potential.